Antike Texte und ihre Materialität Alltägliche Präsenz, mediale Semantik, literarische Reflexion - Ritter-Schmalz, Cornelia; Schwitter, Raphael (Materiale Textkulturen, 2019)
The everyday use of texts in the ancient world relates in many ways to contemporary practice. Besides inscribed artifacts, the self-reflection of Greek and Roman authors demonstrate an awareness of the importance of materiality. This book presents sixteen interdisciplinary studies of specific cases that illuminate this complex interaction between material presence, media semantics, and literary reflection.